Job vacancies in Colombia : 1976-2012 (2013)
Based on the counting of Help-wanted advertisements in print newspapers, we present national vacancy indexes and vacancy rates for Colombia. These series will allow tackling a myriad of questions related to the functioning of the labor markets in emerging economies, where such datasets were not available.